Augustine and World Religions. - Brown, Brian; Doody, John A.; Paffenroth, Kim.; Barnes, Michael; Clooney, Francis X.; Dufault, Olivier; Fredriksen, Paula; Harkins, Franklin T.; Lachance, Paul J.; Lefebure, Leo.; Locklin, Reid.; Pecknold, C. C.; et al. (Lanham : Lexington Books, 2008)
Despite Augustine's reputation as the father of Christian intolerance, one finds in his thought the surprising claim that within non-Christian writings there are 'some truths in regard even to the worship of the One God.' The essays here uncover provocative points of comparison and similarity between Christianity and other religions to further such an Augustinian dialogue.
II. Augustine and Non-Western Religions6 Way and Wilderness: An Augustinian Dialogue with Buddhism Michael Barnes; 7 Augustine, Apuleius, and Hermes Trismegistus: The City of God and Advice on How (Not) to Read Hindu Texts Francis X. Clooney; 8 Wisdom, Compassion, and Charity: The Lotus Sutra and Augustine Leo D. Lefebure; 9 Divine Election as Adhikara and Atma-Sva-Bhava: Rereading the Reply to Simplicianus in Light of a Hindu Text Reid B. Locklin; 10 Transforming the Self: Confession and Performance in the Thought of Augustine and Xunzi Aaron Stalnaker; Biblography; Index; Contributors.
Print version record.
Includes bibliographical references (pages 275-292) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 600
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- Saint, Bishop of Hippo; Christianity and other religions; Augustine, Saint, Bishop of Hippo; Christianity and other religions; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Christianity and other religions; Electronic books